2023
DOI: 10.3390/bs13060449
|View full text |Cite
|
Sign up to set email alerts
|

Active for Life after Cancer: Association of Physical Activity with Cancer Patients’ Interpersonal Competence, Quality of Life, and Survival Beliefs

Abstract: This study aimed to examine the relationship between physical activity and cancer patients’ survival beliefs and constructed a mediation model involving the mediating effects of interpersonal competence and quality of life. We conducted 252 questionnaire surveys on multiple chat groups for cancer patients using the WeChat software, and assessed physical activity, survival beliefs, interpersonal competence, and quality of life using standard scales. Data were analyzed using SPSS and AMOS. There were positive co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Given that universities currently emphasize cultivating students' IC, directly examining the effect of IC on the meaning in life can be more practical. Previous studies have shown that IC can help improve the social adaptation level of adolescents [13], and good IC can relieve depression, reduce pressure, and help enhance the quality of life [14]. People manifesting low IC are prone to be rejected, excluded, isolated, or neglected by others; as their basic psychological needs for belonging and relationships are not met, they may lack positive social connection and meaning in life [15].…”
Section: Introductionmentioning
confidence: 99%
“…Given that universities currently emphasize cultivating students' IC, directly examining the effect of IC on the meaning in life can be more practical. Previous studies have shown that IC can help improve the social adaptation level of adolescents [13], and good IC can relieve depression, reduce pressure, and help enhance the quality of life [14]. People manifesting low IC are prone to be rejected, excluded, isolated, or neglected by others; as their basic psychological needs for belonging and relationships are not met, they may lack positive social connection and meaning in life [15].…”
Section: Introductionmentioning
confidence: 99%